Applying the brakes in tennis: How entry speed affects the movement and hitting kinematics of professional tennis players. Issue 3 (1st February 2021) - Giles, Brandon; Reid, Machar
ABSTRACT: Purpose: Movement and stroke production are coupled when playing tennis but generally decoupled in training and research. This study explored the lower limb, trunk and racquet mechanics of tennis players performing running forehands at varying movement speeds. Methods : Eleven female and seven male professional tennis players hit forehand groundstrokes while travelling at different movement speeds (Low: 1.4–2.0 m s − 1, Medium: 2.70–2.90 m s − 1, High: 4.0–4.3 m s − 1 ). Kinematics were captured using a VICON camera system. Speed and sex effects were analysed using linear mixed-effects models. Results : Prior to impact, females increased drive leg loading kinematics, and reduced preparatory trunk rotation (−9°), while both sexes lengthened their final stride and backswing during high-speed trials. At impact, racquet-head speed was unchanged for male players but dropped 14% when females travelled at high entry speed (p < 0.001). Conclusions : Reduced trunk rotation and lower limb drive contributed to female players being unable to maintain racquet-head speed when moving at high speed. Conversely, male players generated similar racquet-head speed despite the different entry speeds necessitating lower limb joint adjustments. These findings highlight the different deceleration strategies employed by male and female tennis professionals and challenge the widely accepted training theory in tennis that emphasises hitting and moving actions being rehearsed separately.